THE MEDIATING ROLE OF BRAND IMAGE IN DIGITAL MARKETING, E-WOM, AND CELEBRITY ENDORSEMENT EFFECTS - Susilo Utomo; Aan Yulianto; Irene Ferro Cyanida; Andie Paramitha Harianie; Titin Astuti (Universitas Sahid, 2025)
This study aims to analyze the influence of Digital Marketing, Electronic Word of Mouth (e-WOM), and Celebrity Endorser on Purchase Decision with Brand Image as a mediating variable. The study uses a quantitative approach with a descriptive-verification method. Data were collected by distributing questionnaires to 250 respondents who used skincare products selected using an incidental sampling technique. Data analysis was carried out using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method using the SmartPLS 3.0 application. The results of the study indicate that Digital Marketing, e-WOM, and Celebrity Endorser have a positive and significant effect on Brand Image. In addition, e-WOM, Celebrity Endorser, and Brand Image have a positive and significant effect on Purchase Decision, while Digital Marketing shows a significant but negative effect on Purchase Decision. Furthermore, the results of the mediation test prove that Brand Image plays a positive and significant mediator in the relationship between Digital Marketing, e-WOM, and Celebrity Endorser on Purchase Decision. These findings confirm that the effectiveness of digital marketing and endorsement strategies is not only determined by direct influence, but also depends heavily on the company's success in building a strong and credible brand image in the minds of consumers.